Energy Efficient Routing Using Support Vector Machine in Wireless Sensor Networks - Srinivasan, M.; HC, Kantharaju; Govindasamy, Suresh; Rasheed, Mohammad Abdur; Babu P., Ramesh; Sultana, Parveen (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Cluster head selection and energy utilization are efficiently managed using a conventional routing mechanism employing Wireless Sensor Nodes (WSNs). The paper propose a method to enhance network lifetime with an average greater energy utilization. The SVM is used to tackle routing problems in the mobile base station connected with the infrastructure network. The protocol is intended to avoid the control by a centralised router or mobile base station of the complete mobile sensor nodes. In comparison to traditional energy efficient algorithms, the validation of SVM methodology shows an effective routing efficacy. The results against typical routing techniques over WSNs have been found successful.